Common and distinct patterns of terminal modifications to mirtrons and canonical microRNAs - Westholm, Jakub O. (Cold Spring Harbor Laboratory Press, 2012)
Nucleotide modifications to microRNAs or their precursors can influence their processing and/or activity. A challenge to their analysis is the lack of independent references for the termini generated by primary processing; typically, these are empirically assigned as the most abundant mapped reads. Mirtrons offer such an independent measure since these microRNA hairpins are defined by splicing. Consequently, mirtron-derived reads that deviate from splice sites reflect modification following primary processing. Analysis in Drosophila revealed multiple modification patterns, including select alterations of 5′ termini, many 3′ resection events, and unexpectedly abundant 3′ untemplated monouridylation. Resections occur on mature AGO1-loaded species, whereas uridylation occurs on pre-miRNAs but is compatible with dicing and AGO1 loading. Strikingly, we found many mirtrons whose modified reads are more abundant than those produced by primary processing. In some cases, these abundant modified reads matched the genome owing to fortuitous uridines in downstream flanking exons, thus highlighting the value of an independent reference for the primary-processed sequence. We could further extend the principle of abundant and preferred uridylation of mirtrons, relative to canonical pre-miRNAs, to Caenorhabditis elegans, mouse, and human. Finally, we found that 3′ resection occurs broadly across AGO1-loaded canonical miRNA and star species. Altogether, these findings substantially broaden the complexity of terminal modification pathways acting upon small regulatory RNAs.